Kerusakan Lingkungan Dalam Perspektif Al-Qur'an: Tinjauan Literatur Terhadap Qs. Ar-Rum Ayat 41 - Abiyyu Septiandi; Kayla Aida Fitri; Rifaldi Ritamil Sipahutar; Syah Luna Elvanti Sinaga; Yulita Filyanda; Nayla Aira Dharma Putri; Aliqah Ayu Azzahra Siregar; Hani Salsabila; Siti Nailatun Nazila; Naufal Azis; Aditya Pramana Putra Ginting; Nayla Zahra (CV. SINAR HOWUHOWU, 2026)
Contemporary environmental degradation has reached the stage of a global climate crisis and hydrological cycle disruption, threatening ecosystem stability and acting as a primary determinant of declining public health status. This study aims to deeply examine the concept of environmental damage through the theological lens of Surah Ar-Rum Verse 41 using a comparative study of interpretation, and analyze its relevance to modern environmental health issues. Utilizing a literature review method with a descriptive-analytical approach, data were gathered from prominent exegesis books such as Tafsir Al-Azhar and Tafsir Al-Misbah, as well as scientific literature related to Islamic ecology and public health. The review indicates that Surah Ar-Rum Verse 41 explicitly identifies human exploitative behavior, greed, and the loss of moral awareness as the root causes of natural destruction (bima kasabat aidinnas). In the public health perspective, the manifestations of this damage, such as the climate crisis and clean water scarcity, directly trigger tangible harm, including the expansion of vector-borne and water-borne disease transmissions. In conclusion, Islam views environmental preservation as a theological mandate, where the implementation of Islamic ecological ethics becomes an essential behavioral instrument in preventing global harm to maintain public welfare and health status (mashlahah mursalah).